Evaluation of the Impact of Project-Based Vocational Learning Programs at Vocational Schools - Rizkylillah, Muhammad Sadam; Soeprijanto, Soeprijanto; Muksin, Muksin (Universitas Negeri Malang, 2025)
This study evaluates the impact (effectiveness and outcome) of project-based vocational learning program in Electrical Power Installation programs (TITL) at vocational schools in Tangerang, Indonesia. Using the Goal Free Evaluation model and a mixed-methods approach, quantitatively, the study found that 93,93% of the program ran well. It identified 33 positive impacts that matched the program's goals, 2 negative impacts, and 6 unexpected positive outcomes for students such as curiosity, confidence, safety awareness, entrepreneurship, responsibility, and honesty. Addressing high vocational graduate unemployment, this research fills a gap by focusing on real impacts rather than predefined goals. The program is recommended to continue with improvements for better results.